1983
DOI: 10.1002/neu.480140107
|View full text |Cite
|
Sign up to set email alerts
|

The identification and localization of a catecholamine in the motor neurons of the lobster cardiac ganglion

Abstract: The cardiac ganglion from Homarus americanus was investigated for the purpose of providing biochemical and histochemical information as to the identity of the neurotransmitter(s) utilized by this system. Three techniques were employed in this study: (1) the glyoxylic acid histofluorescence staining technique (GA), which showed fluorescence characteristic of catecholamines localized in the five motor neurons; (2) high-voltage electrophoresis (HVE) in one dimension followed by ascending chromatography in the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…This suggests that the labeled cells contained DA rather than norepinephrine (NE) or epinephrine, both of which are synthesized from DA. Some reports have indicated that NE and epinephrine do not occur in crustacean neural tissue (Barker et al, 1979;Cooke and Sullivan, 1982); however, other investigations did detect NE in the crayfish central nervous system (Elofsson et al, 1982;Fingerman and Kulkarni, 1993;Ocorr and Berlind, 1983). Also, Schmidt andAche (1994, 1997) found that their DA antibody cross-reacted with NE such that NE (10 Ϫ4 M) preabsorption of the DA antibody caused a loss of DA immunoreactivity in crustacean tissue.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This suggests that the labeled cells contained DA rather than norepinephrine (NE) or epinephrine, both of which are synthesized from DA. Some reports have indicated that NE and epinephrine do not occur in crustacean neural tissue (Barker et al, 1979;Cooke and Sullivan, 1982); however, other investigations did detect NE in the crayfish central nervous system (Elofsson et al, 1982;Fingerman and Kulkarni, 1993;Ocorr and Berlind, 1983). Also, Schmidt andAche (1994, 1997) found that their DA antibody cross-reacted with NE such that NE (10 Ϫ4 M) preabsorption of the DA antibody caused a loss of DA immunoreactivity in crustacean tissue.…”
Section: Introductionmentioning
confidence: 89%
“…The rhythmic activity of CG neurons is, in turn, modulated by acceleratory and inhibitory axons that project from the subesophageal ganglion and by neurohormones released from the pericardial organs (Field and Larimer, 1975;Wilkens, 1995). In addition to its action as a pericardial neurohormone, DA may function as a neurotransmitter released by cardioaccelerator axons at synapses between these cells and CG neurons Kuwasawa, 1992, 1994), or as an intrinsic neurotransmitter within the CG (Ocorr and Berlind, 1983). To date, most investigations have focused on the effects of DA on the heart via changes in CG output, though direct effects of the amine on the myocardium and cardioarterial valves may also be important in cardiovascular regulation (Wilkens et al, 1996).…”
Section: Cardiovascular Systemmentioning
confidence: 97%
“…7; see also Yazawa and Kuwasawa 1994). The presence of dopamine within these fibers may account for earlier biochemical measurements of catecholamines in the lobster cardiac ganglion (Ocorr and Berlind 1983). The localization of THli does not support a role for dopamine as the neurotransmitter of the motor neurons, a function for which L-glutamate is currently a leading candidate (Benson 1981;Cooke 1966;Delgado et al 2000;Yazawa et al 1998).…”
Section: Catecholaminergic Innervation Of the Cardiac Systemmentioning
confidence: 98%
“…5) Dopamine decreases membrane resistance of LGCs and myocardial cells (T. u and K. Kuwasawa, unpublished observations). Dopamine has been detected by HPLC in the cardiac ganglion in Homarus (Ocorr and Berlind 1983). Sullivan et al (1977) reported that in Panulirus interruptus the dorsal nerve apparatus accumulated nearly half as much dopamine as octopamine, whereas in the ligamental nerve plexuses the range was from 3.4-5.3%.…”
Section: Acceleratory Nervesmentioning
confidence: 99%